Pemberlakuan Asas Presumption Of Innocence Terhadap Penindakan Teroris Di Indonesia - Muhammad Kurniawan Budi Wibowo; Aditya Fajri Kurnia Pradana; Hakim, Luqmanul (Indonesian Journal of Criminal Law, 2024)
This study aims to analyze the principle of the presumption of innocence which is a principle with the aim of ensuring the fulfillment of the rights of every individual to obtain justice and equality in the criminal justice process carried out by law enforcement officers in Indonesia. The research method used is normative juridical with a descriptive analytical approach. The results of the study indicate that the implementation of the principle of the presumption of innocence has not been fully implemented as evidenced by the frequent repressive actions of law enforcement officers, such as shootings on the spot, which have given rise to various legal and social polemics. In conclusion, there needs to be a stricter control mechanism to balance legal interests and human rights so that every individual who commits a crime, including perpetrators of terrorism, still gets equality before the law. Thus, Indonesia as a country of law can still maintain its integrity to uphold human rights and fight the threat of terrorism that threatens the safety of society.